2021
DOI: 10.7554/elife.68447
|View full text |Cite
|
Sign up to set email alerts
|

Acid-base transporters and pH dynamics in human breast carcinomas predict proliferative activity, metastasis, and survival

Abstract: Breast cancer heterogeneity in histology and molecular subtype influences metabolic and proliferative activity and hence the acid load on cancer cells. We hypothesized that acid-base transporters and intracellular pH (pHi) dynamics contribute inter-individual variability in breast cancer aggressiveness and prognosis. We show that Na+,HCO3--cotransport and Na+/H+-exchange dominate cellular net acid extrusion in human breast carcinomas. Na+/H+-exchange elevates pHi preferentially in estrogen receptor-negative br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 83 publications
(155 reference statements)
5
31
0
Order By: Relevance
“…30,34,35 We previously showed that acid-base parameters recorded in organoids freshly isolated from human breast cancer tissue can predict proliferative activity and metastasis. 36 Our current investigation shows that acutely isolated breast organoids and colon crypts can be used for evaluating intracellular Ca 2+ dynamics (Figures 1-4) and study consequences for cell proliferation and survival (Figure 5). Based on our collective previous and current work, the approach of studying freshly isolated human and murine tissue preparations-that retain a profile accurately reflecting the clinical condition-is very well suited for evaluating carcinogenesis-related adaptations and for screening pharmacological agents for functional activity.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…30,34,35 We previously showed that acid-base parameters recorded in organoids freshly isolated from human breast cancer tissue can predict proliferative activity and metastasis. 36 Our current investigation shows that acutely isolated breast organoids and colon crypts can be used for evaluating intracellular Ca 2+ dynamics (Figures 1-4) and study consequences for cell proliferation and survival (Figure 5). Based on our collective previous and current work, the approach of studying freshly isolated human and murine tissue preparations-that retain a profile accurately reflecting the clinical condition-is very well suited for evaluating carcinogenesis-related adaptations and for screening pharmacological agents for functional activity.…”
Section: Discussionmentioning
confidence: 80%
“…30,34,35 Although we cannot fully exclude that the enzymatic treatment influences extracellular epitopes and hence the function of membrane proteins, (a) the partial digestion was mild in order to generate organoids rather than single cell suspensions and (b) we have previously shown that-at least for acid-base transporters-functions evaluated in freshly isolated breast cancer organoids resemble those observed in slices of breast cancer tissue. 29,30,34,36 We investigated the organoids immediately after enzymatic digestion without subsequent culture in order to avoid phenotypic changes. The organoids were classified as "normal" or "cancer" based on the location and macroscopic evaluation of the biopsy site.…”
Section: Freshly Isolated Breast Organoidsmentioning
confidence: 99%
“…Increased expression of the copper efflux transporter ATP7A mediates resistance to cisplatin, carboplatin, and oxaliplatin in ovarian cancer cells 43 . Na+, HCO 3 - cotransporter NBCn1 (Slc4a7) is increased in ErbB2-induced breast cancer tissue compared to normal, and disrupting NBCn1 expression delays ErbB2-induced breast cancer development 44 . However, the mechanisms of LRRC8A upregulation as well as the pathways involved in its tumor-promoting role were unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study demonstrated that anagliptin treatment promoted CT-26 apoptosis. Cancer cells control the intracellular balance of acids and bases through mechanisms not used by normal cells, generating a non-physiological extracellular acidic microenvironment ( 34 ). Therefore, the pathological reversal of the pH gradient in the microenvironment of cancer cells is now recognized as a defining feature of these cells ( 35 ).…”
Section: Discussionmentioning
confidence: 99%